Sport Practitioners as Sport Ecology Designers: How Ecological Dynamics Has Progressively Changed Perceptions of Skill “Acquisition” in the Sporting Habitat - Woods, Carl T.; McKeown, Ian; Rothwell, Martyn; Araújo, Duarte; Robertson, Sam; Davids, Keith (Frontiers in Psychology, 2020)
Over two decades ago, Davids et al. (1994) and Handford et al. (1997) raised theoretical concerns associated with traditional, reductionist, mechanistic perspectives of movement coordination and skill acquisition for sport scientists interested in practical applications for training designs. These seminal papers advocated an emerging consciousness grounded in an ecological approach, signalling the need for sports practitioners to appreciate the constraints-led, deeply entangled and non-linear reciprocity between the organism (performer), task and environment subsystems. Over two decades later, the areas of skill acquisition, practice and training design, performance analysis and preparation, and talent development in sport science have never been so vibrant in terms of theoretical modelling, knowledge generation and innovation, and technological deployment. Viewed at an ecological level of analysis, the work of sports practitioners has progressively transitioned toward the facilitation of an evolving relationship between an organism (athlete, team) and its environment (sports competition). This commentary sets out to explore how these original ideas from Davids et al. (1994) and Handford et al. (1997) have been advanced through the theoretical lens of Ecological Dynamics. Concurrently, we provide case study exemplars, from applied practice in high-performance sports organisations, to illustrate how these contemporary perspectives are shaping the work of sports practitioners (sport ecology designers) in practice and performance preparation.